A urbanização e o comportamento da temperatura superficial: uma análise temporal da Região Metropolitana de Belém - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2017)
This study was developed from 1984 to 2015 in the metropolitan region of Belém do Pará, with the objective of evaluating the surface temperature behavior of the metropolitan area of Belém do Pará, with the purpose of adding new subsidies to the development of strategies for the Urban planning of the metropolitan area of Belém, through the use of geographic information systems - GIS and remote sensing as instruments to study the formation of heat islands in the urban environment, mapping the historical evolution of vegetation cover and land use, relating To the trajectory of urban growth with the consequent changes in the landscape and the process of land use. This objective was accomplished through the use of geotechnologies, specifically in the methodological procedure of supervised classification of Landsat 5 and 8 satellite images to elaborate the mapping of land use and cover, besides this the normalized vegetation index (NDVI) was also applied. To obtain through the mapping the evolution of the vegetation cover during the study period in order to understand the process of deforestation and its implications in the formation of heat islands and in the increase of surface temperature, to understand this variable, the extraction procedure of the Temperature gradient in ° C. All these procedures were developed in specific programs, applied to the analysis from remote sensors. The results were obtained successfully, verifying the behavior of the vegetation over more than thirty years, identifying the critical areas of deforestation and relating the areas of exposed soil and the increase of urbanization and urban growth with the formation of heat islands, In addition, it was found that the vegetation regressed significantly, and the exposed soil area more than tripled from 8% in 1984 to 32% in 2015 and that in such areas the temperature ranges from 31 to 51.1 ° W.
Keywords: Sensoriamento remoto – Belém (PA); . Monitorização ambiental – Belém (PA); Climatologia urbana – Belém (PA).; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS